2017
DOI: 10.1159/000478685
|View full text |Cite|
|
Sign up to set email alerts
|

Knockdown of ARK5 Expression Suppresses Invasion and Metastasis of Gastric Cancer

Abstract: Background/Aims: Gastric cancer (GC) is a common and lethal malignancy, and AMP-activated protein kinase-related kinase 5 (ARK5) has been discovered to promote cancer metastasis in certain types of cancer. In this study, we explored the role of ARK5 in GC invasion and metastasis. Methods: ARK5 and epithelial-mesenchymal transition (EMT)-related markers were determined by immunohistochemistry and western blot in GC specimens. Other methods including stably transfected against ARK5 into SGC7901 and AGS cells, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 35 publications
2
39
0
Order By: Relevance
“…Experiment protocol was performed as described previously [25,26]. Cells were lysed with RIPA lysis buffer.…”
Section: Immunoprecipitation and Western Blottingmentioning
confidence: 99%
“…Experiment protocol was performed as described previously [25,26]. Cells were lysed with RIPA lysis buffer.…”
Section: Immunoprecipitation and Western Blottingmentioning
confidence: 99%
“…As numerous genetic changes are in relation to cancer cell invasion and metastasis,14, 19, 20, 21, 22 great efforts have been made in the identification of novel key regulators and the potential mechanisms involved in this process over the years. Interestingly, recent studies have revealed that CRYAB is aberrantly overexpressed in various types of cancer, and its expression could promote cell invasion and metastasis 8, 9, 10.…”
Section: Discussionmentioning
confidence: 99%
“…As numerous genetic changes are in relation to cancer cell invasion and metastasis, 14,[19][20][21][22] possibly by targeting CRYAB-mediated cell motility. 9 Obviously, these findings provide evidence delineating the pivotal role of CRYAB in cancer invasion and metastasis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cheng et al found that the Akt pathway was involved in mTOR/p70S6k signaling pathway, which is crucial in epithelial mesenchymal transformation (EMT) 31 . Furthermore, Chen et al also provided an evidence of ARK5 involvement in Akt/mTOR/p70S6k signaling pathway, which induced invasion and metastasis of gastric cancer 32 .…”
Section: Role Of Ark5 In Pi3k/akt Pathwaymentioning
confidence: 96%